Crocetin and crocin synthesis via pathway gene expression in the genome of Saccharomyces cerevisiae - 정송연 (The Graduate School, Ajou University, 2024)
Crocin, a natural yellow apocarotenoid, is widely used in the food industry as a valuable spice and colorant. It naturally accumulates in specific tissues of certain plants, such as the saffron stigmas of Crocus sativus and the fruits of Gardenia jasminoides. Recent research has revealed that it has potential therapeutic effects against Alzheimer's disease and that it has strong pharmacological advantages, including anticancer, anti-inflammatory, and antioxidant properties. However, the complex harvesting process, low yields, and the intricacies of its chemical structure present significant challenges to its production. In this study, we developed a biosynthetic pathway for crocin using genetically engineered Saccharomyces cerevisiae, which is widely recognized as an important model for terpenoid production due to its high sugar conversion capability. Initially, the pathway leading to ergosterol was attenuated, and the GGPP pool was increased by overexpressing precursor genes, resulting in enhanced zeaxanthin production. Subsequently, carotenoid cleavage dioxygenase (CCD2) from Crocus sativus was introduced into a zeaxanthin- producing strain to produce crocetin dialdehyde. Next, aldehyde dehydrogenase (ALDH) from Crocus sativus was introduced into the crocetin dialdehyde-producing strain, thereby creating a crocetin-producing strain. Furthermore, two types of UDP-glucosyltransferases (UGTs) were introduced into the crocetin-producing strain to produce crocin in flask culture. To enhance the production of the final product, crocin-4, three genes involved in the endogenous uridine diphosphate glucose pathway, PGM1, PGM2, and UGP1, were overexpressed, resulting in an increase in crocin-4 production from 149 ± 15.52 μg/L to 172 ± 2.05 μg/L in flask cultivation. Finally, through batch fermentation, crocin-4 production reached a maximum of 231 ± 42.11 μg/L. In conclusion, we have established the first biosynthetic pathway for crocin-1/2/3/4 production in Saccharomyces cerevisiae through genome integration.
학위논문(석사)--분자과학기술학과,2024. 8
Keywords: Crocetin; Crocin